SIFAT KIMIA TANAH PADA HUTAN MANGROVE DI DESA TOLAI BARAT KECEMATAN TORUE KABUPATEN PARIGI MOUTONG - a, Asnindar; Korja, I Nengah; r, Rukmi (Universitas Tadulako, 2019)
Mangrove forest vegetation in Indonesia is known for its high species diversity. Diverse mangrove vegetation can provide a good contribution to the soil including soil chemical properties such as soil pH, C-organic, nitrogen, phosphorus, potassium and cation exchange capacity. This research was conducted from January to March 2019, located in the West Tolai Village, Torue District, Parigi Moutong Regency. The purpose of this study was to determine the chemical nature of the soil in mangrove forests in Tolai Barat Village, Torue District, Parigi Moutong Regency. The method used is the survey / observation method and soil sampling is done intentionally (purposive sampling). Sampling was carried out in 3 different conditions, which were always inundated, inundated at moderate tides and inundated at high tides at depths of 0-30 and 30-60 cm, and at each point 3 samples were taken so that a total of 18 samples were composite into 6 the sample. Soil samples are then analyzed in the soil science laboratory. The results of this study indicate that the chemical properties of the soil in the mangrove forest of Tolai Barat Village are very diverse in the three different location conditions, which are always inundated, flooded during medium tides and submerged during high tides with depths of 0-30 and 30-60 respectively. cm has a acidic and neutral soil pH with a value of 4.74 -7.46H2O, C-organic from very low to high 0.45-4.75%, N-Total from moderate to low 0.21-0.05%, P-available is very low 9.11-7.94 ppm, K-Total with low to moderate values 15.89-23.18mg100gr-1, Cation Exchange Capacity (CEC) is classified as very low to low 4.16 -5.88 (cmol (+) kg-1).